Uma teoria semicompatibilista sobre responsabilidade moral : John Fischer e o controle de direcionamento - Fonseca, Tania Schneider da (Universidade do Vale do Rio dos Sinos, 2018)
What are the necessary and sufficient conditions for the moral responsible agency? Many answers to this question have been given in the recent history of philosophy. On the one side, some philosophers believe that the criterion specifying these conditions could be compatible with the determinist’s worldview. On the other side, there are those who deny that this criterion and the determinist’s position could be ever reconciliated. Traditionally, freedom as a capacity to do otherwise has been defended as a necessary condition for moral responsibility. In 1969, when “Alternative Possibilities and Moral Responsibility” (1969) was published, Harry Frankfurt changed the course of the discussion about the free will problem. Frankfurt showed, through some thought experiments, agents that, he argued, were moral responsible for their actions even though they could not have acted otherwise. Frankfurt’s essay pushed several philosophers, remarkably John Fischer, to rethink the problem of moral responsibility. For Fischer, Frankfurt showed that the debate should not be about the compatibility between freedom and determinism, but rather should address the question of whether moral responsibility is compatible with determinism. To deal with this problem, and to further qualify Frankfurt’s position, Fischer develops, as he calls it, a semicompatibilist position. This position, he claims, successfully address the objections from the incompatibilists, thus showing that moral responsibility is compatible with determinism. This study is an investigation of this position. The thesis defended is that the semicompatibilism proposed by Fischer does indeed answers the main incompatibilist’s objections, and it is better than the traditional compatibilist position, which argues that the capacity to do otherwise is a necessary condition for moral responsibility.
Keywords: Responsabilidade moral; Liberdade; Determinismo; John Fischer; Compatibilismo; Incompatibilismo; Semicompatibilismo; Moral responsibility; Freedom; Determinism; John Fischer; Compatibilism; Incompatibilism; Semicompatibilism; ACCNPQ::Ciências Humanas::Filosofia